THE IMPORTANCE OF THE IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEMS IN THE BUSINESS SECTOR - Rahmah, Himah Naely; Mursid, Mansur Chadi; Misidawati, Dwi Novaria; Hamid, Abdul; Lestari, Ika; Gunawan, Ade (Journal of Information System, Applied, Management, Accounting and Research, 2025)
In the rapidly growing digital era, the implementation of Management Information Systems (SIM) is a crucial factor in increasing business efficiency and competitiveness. This study aims to analyze the importance of SIM implementation in the business sector and its impact on operational effectiveness and strategic decision-making. The research method used is a quantitative approach with a survey of various companies that have adopted driver's licenses. The results show that the implementation of SIM contributes significantly to improving operational efficiency, accelerating the decision-making process, and increasing customer satisfaction through more systematic data management. In addition, the study identified key challenges in SIM implementation, such as the cost of initial investment and resistance to change within the organization. Thus, a deeper understanding of the benefits and challenges of SIM implementation can assist companies in designing more effective strategies to optimize their business performance.